Primary Hyperaldosteronism is An Unusual Cause of Periodic Paralysis: A Case Report - Rahman, Aminur; Hossain, Md Alamgir; Dastegir Khan, Shahjada Mohammad; Paul, Biplab; Saha, Pallab Kanti; Agarwalla, Ajay Kumar; Mishu, Mahbubul Hakim; Proma, Sanghita Banik; Arefin, Sams; Twinkle, Furial Quraishi; Ahmed, Tofael (Bangladesh Journal of Medicine, 2024)
Primary hyperaldosteronism a synonym for Conn's syndrome is characterized by hypernatremia, arterial hypertension, and, in certain situations, potentially fatal hypokalemia. A rare class of neuromuscular disorders known as periodic paralysis (PP) is brought on by an affection of the skeletal muscle's ion channels. In patients with hypokalaemic PP, potassium levels are normal in between attacks, but they remain low in those with secondary hypokalaemic PP. Although secondary causes of PP have been documented in the literature, the majority of cases are hereditary. We report the case of a 46-year-old man who had a history of hypertension and was admitted to the neurology ward after experiencing sudden-onset weakness in all four limbs, primarily affecting the lower limbs, two days earlier. This present case demonstrates a peculiar and severe primary hyperaldosteronism manifested by PP. Bangladesh J Medicine 2024; 35(1): 42-46